2013 Proceedings of the International Conference on Embedded Software (EMSOFT) 2013
DOI: 10.1109/emsoft.2013.6658598
|View full text |Cite
|
Sign up to set email alerts
|

StreaMorph: A case for synthesizing energy-efficient adaptive programs using high-level abstractions

Abstract: This paper presents the concept of adaptive programs, whose computation and communication structures can morph to adapt to environmental and demand changes to save energy and computing resources. In this approach, programmers write one single program using a language at a higher level of abstraction. The compiler will exploit the properties of the abstractions to generate an adaptive program that is able to adjust computation and communication structures to environmental and demand changes.We develop a techniq… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2014
2014
2014
2014

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 30 publications
(23 reference statements)
0
4
0
Order By: Relevance
“…It uses the fusion and fission operators to generate a schedule that maximizes the throughput of the application. StreaMorph [2] is a technique to adapt SDF graphs at run-time by performing a reverse sequence of executions to bring the graph into a known state. In contrast to the previous two approaches, our technique does not assume a static schedule and is therefore applicable to more complex MoCs than SDF graphs.…”
Section: Related Workmentioning
confidence: 99%
See 2 more Smart Citations
“…It uses the fusion and fission operators to generate a schedule that maximizes the throughput of the application. StreaMorph [2] is a technique to adapt SDF graphs at run-time by performing a reverse sequence of executions to bring the graph into a known state. In contrast to the previous two approaches, our technique does not assume a static schedule and is therefore applicable to more complex MoCs than SDF graphs.…”
Section: Related Workmentioning
confidence: 99%
“…Specially, we address this challenge in the context of streaming applications, which are modeled as process networks. In fact, previous works showed that large performance gains in terms of throughput [17,20] or energy consumption [2] can be obtained if the process network is refined at compile-time.…”
Section: Introductionmentioning
confidence: 98%
See 1 more Smart Citation
“…It is shown in the context of the StreamIt language [18] that the combination of pipeline parallelism and coarse-grained data parallelism is important [1]. Other methods acknowledge the benefits of the combination of data and pipeline parallelism [19], [20] and use dataflow models to analyze the temporal behavior of data parallel tasks. However, none of these methods determines the amount of data parallelism that is required to meet the throughput constraint of an application.…”
Section: Related Workmentioning
confidence: 99%